Pathological nodal disease defines survival outcomes in patients with lung cancer with tumour major pathological response following neoadjuvant chemotherapy. (30th August 2020) - Corsini, Erin M; Weissferdt, Annikka; Pataer, Apar; Zhou, Nicolas; Antonoff, Mara B; Hofstetter, Wayne L; Mehran, Reza J; Rajaram, Ravi; Rice, David C; Roth, Jack A; Vaporciyan, Ara A; Walsh, Garrett L; et al.
Abstract: OBJECTIVES: Major pathological response (MPR) is prognostic of outcomes for patients with non-small-cell lung cancer following neoadjuvant chemotherapy and is used as the primary end point in neoadjuvant immunotherapy trials. We studied the influence of pathological nodal disease on patterns and timing of recurrence among patients with MPR. METHODS: Patients treated with neoadjuvant chemotherapy for stages I–III non-small-cell lung cancer were identified. Surgical specimens were histopathologically examined for tumour viability, categorized as ≤10% viability (MPR) or >10% (NoMPR). Overall survival and disease-free survival were evaluated with emphasis upon MPR and pathological nodal disease. RESULTS: Among 307 patients, 58 (19%) had MPR within primary tumour and 42 (14%) had MPRypN0. In the MPR group, the frequency of cN0 and cN+ disease was 18 (31%) and 40 (69%); similarly, the frequency of ypN0, ypN1 and ypN2 was 72% (42/58), 16% (9/58) and 12% (7/58), respectively. When evaluating only those with MPR, recurrence rates among those with MPRypN0, MPRypN1 and MPRypN2 were 33% (14/42), 44% (4/9) and 71% (5/7) ( P  =   0.16). The median time-to-recurrence in MPRypN0, MPRypN1 and MPRypN2 was 40, 10 and 14 months ( P  =   0.006). Distant recurrences were less common among those with MPRypN0 [MPRypN0, 26% (11/42); MPRypN1, 44% (4/9); MPRypN2, 71% (5/7); P =  0.047]. Though the median disease-free survival was prolonged among those with MPR vs NoMPR (120 vs 25 months, P  <   0.0001), only those with MPRypN0 had prolonged disease-free survival in comparison to other groups upon pairwise comparisons, while MPRypN+ experienced no benefit. CONCLUSIONS: MPRypN0 represents the most favourable surrogate end point following neoadjuvant chemotherapy. Patients with ypN1-2 are at the risk of early recurrence regardless of primary tumour MPR, warranting intensive surveillance and consideration for additional adjuvant therapy. We highlight that MPRypN0 is the most rigorous end point and should be considered as a surrogate end point in future neoadjuvant trials.